2019
DOI: 10.1177/1470320319882656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dual blockade in heart failure and renal dysfunction: Systematic review and meta-analysis

Abstract: Objective: The effect of dual renin–angiotensin system (RAS) inhibition in heart failure (HF) is still controversial. Systematic reviews have shown that dual RAS blockade may reduce mortality and hospitalizations, yet it has been associated with the increased risk of renal dysfunction (RD). Surprisingly, although RD in patients with HF is frequent, the effect of combining RAS inhibitors in HF patients with RD has never been studied in a meta-analysis. Methods: A systematic review and meta-analysis of randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…ACEis, ARBs or aliskiren should not be combined because no added benefit on CV outcomes has been shown by dual RAS inhibition [559]. Although double RAS blockade has been shown to have a greater antialbuminuric effect and might have favorable effects in HF, the association may cause an excess of adverse events, with an increased risk of kidney function impairment (40%), hyperkalemia (44%) and hypotension (42%) [560] in patients with a high CV risk [559] or type 2 diabetes [561]. Co-medications susceptible to significant drug interactions mediated by P-gp or CYP3A4 for eplerenone…”
Section: Combination Of Ras Inhibitorsmentioning
confidence: 99%
“…ACEis, ARBs or aliskiren should not be combined because no added benefit on CV outcomes has been shown by dual RAS inhibition [559]. Although double RAS blockade has been shown to have a greater antialbuminuric effect and might have favorable effects in HF, the association may cause an excess of adverse events, with an increased risk of kidney function impairment (40%), hyperkalemia (44%) and hypotension (42%) [560] in patients with a high CV risk [559] or type 2 diabetes [561]. Co-medications susceptible to significant drug interactions mediated by P-gp or CYP3A4 for eplerenone…”
Section: Combination Of Ras Inhibitorsmentioning
confidence: 99%
“…These results suggest that dual RAS blockade reduced the risk of cardiovascular death and hospitalization for heart failure but did not increase the risk of renal damage. However, specific adverse events must be monitored during treatment [41]. In a RCT, Saglimbene et al [42] reported that patients may tolerate ARBs better than ACEIs.…”
Section: The Efficacy and Safety Of Dual Renin-angiotensin System Blomentioning
confidence: 99%